TINJAUAN KRITIS HUKUM PIDANA TERHADAP MEDIA PENYIARAN YANG BERDAMPAK PADA TINGGINYA TINDAK KRIMINALITAS DI INDONESIA - Herwin Sulistyowati (Jurnal Pembaharuan Hukum, 2016)
The development of broadcast media in Indonesia is relatively rapid, with many institutions have sprung up television and radio. The effect of the dominant society because some people almost time spent watching television is. do not be surprised if anyone wants to put his desires leewat, broadcast this. Although Law No. 32 of 2002 on Broadcasting has granted the protection of the law, but in terms of restrictions and oversight to date does not seem serious and less. So many impressions should not deserve to be shown, and in fact could be in the realm of criminal because it was forced to watch public undesirable. The number of cases of murder, rape, drug-like effect is not spared from watching television, far from the reach of entrepreneurs. How sad when screening for children crammed with cartoon pictures of a princess dress half body, or run a criminal offense is still wearing the "blur", though disguised, but still leaves a curiosity. Criminal Policy is expected to give the desired result, but also in the sense of considering the effectiveness of criminal sanctions for the benefit approach.